Population status of black and white rhinos in Zambia - Chomba, Chansa; Matandiko, Wigganson (Pachyderm, 2011)
Poaching was the primary cause of extermination of black rhinos in Zambia. From an estimated population of 12,000 individuals in the 1960s, the population declined to extinction by 1993. Reported incidences of spoors and unverified sightings of individuals continued to be reported to the Zambia Wildlife Authority but none of these reports was verified and the species was assumed to be locally exterminated by 1995. In 2003 a National Rhino Conservation Plan was formulated and in the same year, with the technical guidance of the Rhino Specialist Group and financial support of the Frankfurt Zoological Society a rhino reintroduction programme begun. To date there are 27 black rhinos with six births and four mortalities recorded. None of the mortalities were due to poaching. There are plans to continue the reintroduction programme in other national parks where the rhino existed by 1972 when most of the national parks were established. As the black rhino population was being established, the out-of-range white rhino was also introduced in Mosi oa Tunya National Park, where the population size was recorded to be seven and another pair was introduced in the newly established Lusaka National Park No. 20 in March 2011. Keywords: black rhino, white rhino, reintroduction, North Luangwa, conservation plan Le braconnage a été la principale cause de l’extermination des rhinocéros noirs en Zambie. A partir d’une population estimée à 12.000 individus dans les années 1960, la population a diminué jusqu’à l’extinction en 1993. Les incidents d’empreintes et dÊobservations non vérifiées d’individus ont continué à être signalés au siège de l’Autorité de la Faune de Zambie à Chilanga, mais aucun de ces rapports n’a été vérifié et enfin en 1995 l’espèce était présumée être localement exterminée. En 2003, un plan national de conservation des rhinocéros a été formulé et dans la même année, avec les conseils techniques du Groupe de spécialistes du rhinocéros et le soutien financier de la Société zoologique de Francfort, un programme de réintroduction de rhinocéros a commencé. A ce jour il y a 27 rhinocéros noirs et on a enregistré six naissances et quatre mortalités. Aucune des mortalités n’était due au braconnage. On prévoit de poursuivre le programme de réintroduction dans dÊ’utres parcs nationaux où les rhinocéros existaient à l’époque de la création des parcs nationaux, il y a environ 40 ans. Pendant que la reconstitution de la population des rhinocéros noirs se poursuivait, on introduisait également le rhinocéros blanc exogène dans le Parc national de Mosi oa Tunya, où l’on a enregistré une taille de population de sept individus et un autre couple a été introduit dans le nouveau parc national No. 20 de Lusaka en mars 2011.